Respuesta :

[tex] \sf \: 3x + x \sqrt{3} - 2 = 0 \\ \\ \sf \longrightarrow 3x + \sqrt{3} x = 2 \\ \\ \sf \longrightarrow \sqrt{3}x ( \sqrt{3} +1 ) = 2 \\ \\ \sf \longrightarrow \sqrt{3} x = \frac{2}{ \sqrt{3} + 1 } \\ \\ \sf \longrightarrow x = \frac{2}{ \sqrt{3}( \sqrt{3} + 1) } \\ \\ \sf \longrightarrow x = \frac{2}{3 + \sqrt{3} } \\ \\ \tt{You\:can\:stop\:here\:if\:you\:\bold{don't}\:want\:to }\\ \tt{ \:simplify\:in\:decimal\:form.}\\ \\ \sf \longrightarrow x = \frac{2(3 - \sqrt{3} )}{(3 + \sqrt{3})(3 - \sqrt{3} )} \\ \\ \sf \longrightarrow x = \frac{6 - 2 \sqrt{3} }{ {3}^{2} - {( \sqrt{3}) }^{2} } \\ \\ \sf \longrightarrow x = \frac{6 - 2(1.732)}{9 - 3} \\ \\ \sf \longrightarrow x = \frac{2.536}{6} \\ \\ \leadsto \underline{\boxed{\sf{\pink{x \approx 0.4226}}}}[/tex]

ACCESS MORE